Obesity-Associated Sleep Hypoventilation and Concomitant Severe Obstructive Sleep Apnea - Lin, Jin-Ing (Journal of sleep medicine, 2025)
Hypoventilation in obesity has four stages, and the first two stages are associated with intermittent nocturnal hypercapnia. We report a 46-year-old man who belongs to Stage 1, with complete washout of nocturnally accumulated carbon dioxide (CO2) and associated concomitant severe obstructive sleep apnea and severe hypoxemia. That condition will lead to progressive right heart dysfunction secondary to persistently nocturnal impaired ventilation and hypoxemia via the pathomechanism of hypoxic pulmonary vasoconstriction and pulmonary vascular remodeling by cytokines and growth factors, supposedly once it is missed for early diagnosis and appropriate PAP therapy is not introduced in time. Early identification and diagnosis of such conditional disease and in-time appropriate treatment are very important before sequelae of disease develop so that we could be able to prevent cardiovascular morbidity and mortality before disease progression.